2012
DOI: 10.1159/000334157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citrate Acid Concentrate (Citrasate®) on Heparin N Requirements and Hemodialysis Adequacy: A Multicenter, Prospective Noninferiority Trial

Abstract: Background: Citrasate®, citric acid dialysate (CD), contains 2.4 mEq of citric acid (citrate), instead of acetic acid (acetate) as in standard bicarbonate dialysate. Previous studies suggest CD may improve dialysis adequacy and decrease heparin requirements, presumably due to nonsystemic anticoagulant effects in the dialyzer. Methods: We prospectively evaluated 277 hemodialysis patients in eight outpatient facilities to determine if CD with reduced heparin N (HN) would maintain dialyzer clearance. Subjects pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 17 publications
3
60
3
8
Order By: Relevance
“…In these studies, however, anticoagulation with heparin was maintained at the usual dose [6,8] or the dialyzer was reused [20]. Our results are similar to those obtained by Sands et al [11] comparing conventional hemodialysis treatments with a citrate dialysate and reduced doses of heparin. Ionic dialysance remained stable compared to a regular heparin dose and standard acetic acid based dialysate [11].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In these studies, however, anticoagulation with heparin was maintained at the usual dose [6,8] or the dialyzer was reused [20]. Our results are similar to those obtained by Sands et al [11] comparing conventional hemodialysis treatments with a citrate dialysate and reduced doses of heparin. Ionic dialysance remained stable compared to a regular heparin dose and standard acetic acid based dialysate [11].…”
Section: Discussionsupporting
confidence: 86%
“…Studies evaluating the use of CitA-D in conventional hemodialysis usually found a decrease of total and ionized serum calcium during the sessions [6,11,19]. However, the dialysate calcium concentration was 1–1.25 mmol/l against 1.5 mmol/l in our study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Similar to calcium mass balance considerations, dialysis-related sodium loading is another topic that has been receiving more and more attention in recent years and is another domain of solute kinetic modeling that should ultimately be integrated into citrate dialysis modeling, particularly given the additional sodium load administered with the use of regional citrate anticoagulation. The use of dialysate-side citrate anticoagulation (i.e., the use of a citrate-and calciumcontaining dialysate without arterial citrate infusion or venous calcium substitution) has sparked interest recently for its alleged heparin-sparing potential and its safety and ease of use [27][28][29]. At unchanged heparin doses, using citrate-containing dialysate (instead of bicarbonate dialysate acidified with acetate) appears to improve solute removal [30].…”
Section: The Future Of Citrate Anticoagulation In Hemodialysismentioning
confidence: 99%
“…El empleo de líquido dializante con citrato puede incrementar la eficacia del dializador dado su conocido poder anticoagulante 6 , ya que actúa de forma temprana sobre el calcio en la cascada de la coagulación, así como disminuir la precipitación de sales cálcicas al actuar como quelante del calcio iónico. Además de estos beneficios, consigue una mejoría del equilibrio ácido-base dado su efecto tampón y una mayor tolerancia a la sesión de diá-lisis consecuencia de una mayor estabilidad cardiovascular 7 …”
Section: Introductionunclassified